TRANSITIVITY ANALYSIS: GENDER REPRESENTATION IN TWO ENGLISH TEXTBOOKS FOR TENTH GRADE STUDENTS - Salsabila, Vina Aini; Maolida, Elis Homsini; Nuraini, Winda (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2023)
Textbook is learning material that can affect student’s perspective and thinking. Therefore, it is necessary to pay attention to several things such as gender equality contained in the textbook, either explicitly or implicitly. This paper concerns gender representation in two English textbooks assessed by the National Education Standards Agency and Cambridge University Pers. The framework of systemic functional linguistics proposed by Halliday & Matthiessen (2014) is utilized in this study. The research used a qualitative descriptive analysis focusing on the textual data obtained from the 10 selected texts related with the gender roles of the characters. The result indicates that male was found to be more frequently represented in roles of Participants, Process and Circumstantial. In this case, females are almost invisible and marginalized in both textbooks. Four types of transitivity were found in the first book and they represented male as characters whose activities related to business or industry with high desires, rational and a traveler whereas female represented as characters whose activities related to education and household. The second book contains six types of transitivity process, it is represented male as strength, attentive, talk much and female as a nurturing, beautiful, complaisant and cheerful. In summary, there is unequal representation between male and female in both textbooks.